Systematic review of malnutrition risk factors to identify nutritionally at-risk patients with head and neck cancer - Wang, Pengpeng; Soh, Kim Lam; Soh, Kim Geok; Xue, Li; Ning, Chuanyi; Tan, Yanmei; Huang, Xueling (Oncology Nursing Society (ONS), 2024)
BACKGROUND: Patients with head and neck cancer are prone to malnutrition, which can lead to adverse health outcomes. A review of the literature revealed a lack of systematic reviews addressing risk factors for malnutrition in this population. OBJECTIVES: This study aimed to fill the knowledge gap by identifying risk factors for malnutrition in patients with head and neck cancer. METHODS: A comprehensive search was con-ducted in PubMed®, Web of Science, Embase®, and Cochrane Library databases, spanning from their inception until June 2023. Three researchers critically evaluated the inclusion and exclusion criteria. Two investigators independently screened the literature and extracted data, resolving any discrepancies through consensus. FINDINGS: This systematic review includes 18 studies. The results indicated that risk factors for malnutrition in patients with head and neck cancer encompass disease-related, genetic, lifestyle, nutritional health, physiologic, psychological, and treatment-related factors.